Make a Match Type Cooperative Model: An Effort to Improve Student Learning Outcomes in Qur'an Hadith Learning - Gade, Syabuddin (MANDAILING GLOBAL EDUKASIA, 2024)
This research is motivated by the low learning outcomes of the Al-Qur'an Hadith on the material of the law of reading idhar and ikhfa' of class IV Unggul MIN 1 East Aceh. The purpose of this study was to determine the improvement in learning outcomes of the material of the law of reading idhar and ikhfa' through the Make A Match method. This type of research uses Classroom Action Research with four steps, namely planning, action, observation and reflection. This classroom action research was carried out in two cycles. The first cycle was carried out on October 30, 2023 and the second cycle was carried out on November 07, 2023. The research was carried out in class IV Unggul MIN 1 East Aceh with a total of 28 students consisting of 9 male students and 19 female students. The results of the study showed that the Make A Match method can improve learning outcomes on the material of the law of reading idhar and ikhfa' in class IV Unggul MIN 1 East Aceh. The improvement in learning outcomes on the material of the law of reading idhar and ikhfa' is known from the test results in the first and second cycles which showed an increase in the average value and percentage of completion classically. The average score of Al-Qur'an Hadith students in the initial condition (pre-cycle) was 68.6 with classical completeness of 39.2% (11 students) out of 28 students achieving a score of >70 (minimum completeness criteria). Cycle I averaged 80 with classical completeness of 75% (21 students) achieving a score of >70 (minimum completeness criteria). Cycle II averaged 85.8 with classical completeness of 85.8% (24 students) achieving a score of >70 (minimum completeness criteria).